PENGGUNAAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACE UNTUK MENINGKATKAN MOTIVASI BELAJAR IPS SISWA SEKOLAH DASAR - Ambrosius L Edu; Oktavianus Namas Dali (Jurnal Literasi Pendidikan Dasar (JLPD), 2021)
This research is motivated by the problem of low students motivation. The puspose of writing is to determine the effect of using an active learning strategy of trading place type in overcoming the the phenomenon in elementary school. The method used in this research was a literature study research method. This research was used to be able to find sources in collecting data, such as books, scientific journals, articles, theses and newspapers that were relevant to students’ learning motivation in elementary schools. The results of this study indicated that the use of an active learning strategy of the trading place type can overcome the low motivation to learn social studies for elementary school students. Use of the active learning strategy an involve students actively in the learning process because it provides opportunities to get to know, work together, exchange opinions and consider ideas, values or to find new ideas on various problem. This can increase students’ learning motivation and ability to communicate. From the results of the research above, it can be concluded that the use of trading place type active learning strategies can increase students’ motivation to learn social studies in ementary schools.